IMPLEMENTASI RETRIBUSI PELAYANAN PARKIR DI TEPI JALAN UMUM KECAMATAN TUALANG BERDASARKAN PERDA KABUPATEN SIAK NOMOR 21 TAHUN 2011 - Putri, Elsi Radika; Hambali, Hambali; Arianto, Jumili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by problems that arise in the field that are not in accordance with the policy, it is assumed that the service of parking attendants has not been maximized and the imbalance between the number of parking points and the number of parking attendants available in implementing parking levies is certainly unfortunate given the large amount of potential revenue the area obtained by Siak Regency if the amount of human resources to collect parking fees is adequate. In the administration of parking service fees on public roads, constraints arise in the implementation of parking service fees. The lack of local government socialization about the location points of parking service charges on the side of the public road so that many people who use illegal fees (levies) on the subject of parking fees and the ignorance of the subjects about what they pay, about what fees they pay to the government regions increasingly make these individuals carry out payment routines that do not have a clear legal basis in either the law or regional regulations, parking attendants or officers in charge of collecting parking usually raise the rates set by the local government.Key Words: Policy Implementation, Parking Fees, Inhibiting Factors.